Implementasi Pembelajaran Daring Menggunakan Media Kahoot di SMA Sungai Putih Kecamatan Tapung Kabupaten Kampar - Silvia Permatasari; Tengku Hamid Darmawan; Rendy Rendy; Nabila Azzahra; Lola Zulaika; Ummi Asomah; Yunita Feronika Br. Silaban; M. Ashabil Yamin; Sinta Putri Widarti; Anisha Rahayu; Dela Puspita (Pusat Riset dan Inovasi Nasional, 2023)
The Industrial Revolution 4.0, which coincided with the presence of the Covid-19 pandemic, demanded that the world of education implement a different system. Classroom learning that involves students directly is now starting to switch to online learning. One of the learning media used is the Kahoot application. Interactive quizzes in this application can be implemented on an ongoing basis, including in face-to-face learning after the pandemic. Unfortunately, not all educational institutions know about the existence and benefits of this application. Sungai Putih High School, Kampar Regency, which is our service partner, is one of them. This dedication to introducing interactive learning through online media has had satisfactory results. From 38 respondents covering all classes and teachers at the high school, 100% of respondents felt interested in this learning and 96% of respondents agreed that learning evaluation using Kahoot was felt to be more effective than tests in general. For the continuity of implementation, the service team provided a Kahoot Usage Guide book which was designed directly by the service team.